Organizing Educational Processes On The Basis Of Information Technology - DILSHOD YULDASHEV; GULBAKHOR SOLIYEVA (Procedia of Social Sciences and Humanities, 2022)
Our Republic is also moving towards an informed society due to independence. This issue is one of the first issues in the focus of our President and government. Today, the Internet has emerged as a fast and reliable source of information. The development of the information world has undergone dramatic changes and new information technologies have emerged. There has been a lot of talk lately about the Internet, its capabilities, and e-mail. The terms "computer" and "internet" are becoming everyday popular terms.